Urgensi Pengaturan Bentuk Perjanjian Tertulis Antara Biro Penyelenggara Umrah Dengan Jemaah Umrah - Hikmah, Aufa Fajrul; Chanifah, Nur; Widhiyanti, Hanif Nur (Universitas Negeri Malang, 2023)
the purpose of writing this article is to discuss the urgency of arranging a written Umrah departure agreement. The study uses a normative juridical method with a statutory approach and an analytical approach. Law Number 18 of 2019 concerning the Implementation of the Hajj and Umrah Pilgrimage does not require written agreements so that problems often arise that are detrimental to the congregation. Collaboration between the bureau and the umrah congregation can run smoothly if the agreement is implemented in writing. This is to reduce the risk of fraud or other things that could harm one or both parties. A written agreement provides more legal certainty and protection to the parties which is used as a guide for the bureau and the congregation to act in accordance with what was promised